Optimal generation scheduling in microgrids using mixed-integer second-order cone programming. Issue 12 (1st December 2020) - Shaghaghi-shahr, Gholamreza; Sedighizadeh, Mostafa; Aghamohammadi, Mohammadreza; Esmaili, Masoud
Abstract : In this article, a new model is proposed for the operation of microgrids (MGs) using optimal distribution feeder reconfiguration (DFR) and optimal generation scheduling (OGS). The distributed generation units, electric vehicles and demand response (DR) are modelled in the presented model. The DR programs consider load shifting, load curtailing and time-of-use programs. The proposed model is formulated as a mixed-integer second-order cone programming problem and solved by the GAMS software package. The total operating cost is taken into account as the objective function and several operational constraints are used in the optimization problem. The simulation results of the 33-bus MG are shown, where considering OGS along with DFR leads to a lower operating cost. In addition, the load shifting of a DR program can reduce the total operating cost by smoothing the load profile and reducing the cost of power purchases from the main grid.